Uma abordagem Vygotskyana para o ensino de polígonos no LEM para estudantes do 8º ano do ensino fundamental - Leal, Leila Beatriz (2023)
Currently, several obstacles in the educational environment hinder the teaching-learning process, causing disruption and dissatisfaction among teachers and students. Mathematics is seen by students as complex and, therefore, they do not strive to obtain satisfactory results. Given these factors, teachers must seek pedagogical alternatives so that students feel motivated to learn. With this in mind, this research aims to promote observations about how geometry teaching can be developed, with the Mathematics Teaching Laboratory (LEM) as an ally, with the aim of providing mathematical teaching based on Vygotsky's theory. Thus, the present study has as its guiding question: What are the contributions of an educational product based on Vygotsky's mediation theory and structured based on the ideas of the LEM for the teaching of geometry in Elementary School? The general objective is to develop, apply and evaluate an educational product based on the mediation theory and structured based on the ideas of the LEM, with a view to assisting teachers in the teaching and learning process of polygons in the 8th grade of Elementary School. The specific objectives are: 1) to understand Vygotsky's mediation theory; 2) to understand the ideas of the LEM; 3) to develop, implement and evaluate a didactic sequence with 8th grade Elementary School students for the study of polygons; 4) to prepare a support text for Elementary School Mathematics teachers, which assists in the teaching process of polygons. The research is based on the mediation theory, which is characterized by the idea that the individual acquires learning through the interactive process with other individuals and with the environment in which he/she is immersed. The research covers the LEM space and the manipulable teaching material as supports for teaching geometry in 8th grade Elementary School classes of a public school in the city of Ariquemes-RO. A teaching sequence structured in seven stages is presented, with 15 class hours of 50 minutes each. The logbook is used as a data collection and recording instrument. Two categories are structured to analyze the data produced: mathematical progress and involvement and interaction in the LEM. Based on the observations and records made during the implementation of the teaching sequence, the results obtained confirm the effectiveness of the methodology employed, indicating that the approach adopted is not only efficient but also viable, suggesting that the proposal can be successfully applied in educational contexts. The methodology adopted proved to be appropriate and relevant, favoring a teaching process deeply connected to the students' reality, promoting interaction, critical reflection and student protagonism. From this perspective, the study gave rise to support material for teachers, which consists of the educational product of this dissertation, available at http://educapes.capes.gov.br/handle/capes/743066.